Wahkohtowin as Paideia (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2018)
The Wahkohtowin class was held in Saskatoon throughout early 2014. Wahkohtowin brought together prisoners, students, and professors, in order to critically examine Canada’s “justice” system. For the author, participation in this class led to deep learning, or what ancient Greeks called Paideia. This article explores why Wahkohtowin led to deep learning. It concludes that the deep learning was attributable to four factors: the leaders created space for suffering to speak; course participants were racially, culturally, and educationally diverse; the pedagogy was relationally Socratic; and participant reflections were aimed at action, in addition to understanding. Throughout the article, Wahkohtowin is compared with the author’s experience of law school in order to highlight why law school courses rarely result in Paideia.